A habitat‐based approach to predict impacts of marine protected areas on fishers. Issue 5 (30th June 2018) - Teixeira, João B.; Moura, Rodrigo L.; Mills, Morena; Klein, Carissa; Brown, Christopher J.; Adams, Vanessa M.; Grantham, Hedley; Watts, Matthew; Faria, Deborah; Amado‐Filho, Gilberto M.; Bastos, Alex C.; Lourival, Reinaldo; et al.
Abstract: Although marine protected areas can simultaneously contribute to biodiversity conservation and fisheries management, the global network is biased toward particular ecosystem types because they have been established primarily in an ad hoc fashion. The optimization of trade‐offs between biodiversity benefits and socioeconomic values increases success of protected areas and minimizes enforcement costs in the long run, but it is often neglected in marine spatial planning (MSP). Although the acquisition of spatially explicit socioeconomic data is perceived as a costly or secondary step in MSP, it is critical to account for lost opportunities by people whose activities will be restricted, especially fishers. We developed an easily reproduced habitat‐based approach to estimate the spatial distribution of opportunity cost to fishers in data‐poor regions. We assumed the most accessible areas have higher economic and conservation values than less accessible areas and their designation as no‐take zones represents a loss of fishing opportunities. We estimated potential distribution of fishing resources from bathymetric ranges and benthic habitat distribution and the relative importance of the different resources for each port of total catches, revenues, and stakeholder perception. In our model, we combined different cost layers to produce a comprehensive cost layer so that we could evaluate of trade‐offs. Our approach directly supports conservation planning, can be applied generally, and is expected to facilitate stakeholder input and community acceptance of conservation. Abstract : Article impact statement : Habitat‐based estimates of opportunity costs to fishers inform conservation planning